MENILAI NIAT PERILAKU MAHASISWA UNTUK MENGGUNAKAN ILIAS SEBAGAI PLATFORM PEMBELAJARAN DARING MENGGUNAKAN MODEL UTAUT2 - Sarmini Sarmini; Niken Lia Prihatiningtias Pambayun; Nilam Puspita Nurdewanti (LPPM STMIK STIKOM Indonesia, 2021)
The use of e-learning in the learning process at Amikom Purwokerto University has been implemented since early 2019 by utilizing the ILIAS e-learning platform. The problem that arises is whether students are satisfied and intend to continue using the ILIAS platform for the online learning process during the pandemic period and afterwards where there are still many obstacles experienced by students during online lectures. This study aims to assess the behavioral intention of Amikom Purwokerto University students to use ILIAS as an online learning platform by adopting the UTAUT2 (Unified Theory of Acceptance and Use of Technology 2) model. Based on the results of hypothesis testing, it shows that each variable has a significant effect and has a significant impact on the use of ILIAS, this is evidenced by each hypothesis being accepted with a t-value> 1.96. Based on the t-value, the variable Performance Expectancy, Facilitating Condition and Habit is the variable with the highest t-value among the other variables, namely (PE -> BI = 16.8709), (FC -> UB = 13.4742) and (HB - > UB = 12.6896). This shows that these three variables have a high significant influence and impact on the use of ILIAS. In further research, it may be possible to consider the use of moderating variables such as age, gender, experience, and so on or add other variables such as Security and Information Quality.